Vesicocervical fistula: a case report - Cortés, Diana del C. P.; Cabrales, Filiberto M.; Penilla, Luisa F. R.; González, Alejandro C. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
We present a case report of a vesicocervical fistula in a 70-year-old female with history of caesarean section forty-five years prior to clinical presentation, she presented referring continuous vaginal urinary incontinence of a couple of years of evolution, the diagnosis of delayed presentation vesicocervical fistula associated with a caesarean section was reached by exclusion, after ruling out infectious or malignant pathologies. An abdominal approach with hysterectomy and extra vesical fistulectomy was performed without any complications during the procedure. At follow-up blue dye test was negative and continuous urinary incontinence resolved. We present an alternative management of an extremely rare presentation of urogenital fistulae.